ROMAN ARMY AND SALT EXPLOITATION IN DACIA - Lucretiu Mihailescu-Birliba; Andrei Asăndulesei (Journal of Ancient History and Archaeology, 2019)
The authors study the connections between salt resources, salt exploitation and Roman army in Dacia. Even though salt resources are attested almost across the entire province of Dacia (excepting perhaps the western part), the eastern part is the richest not only in salt deposits, but also salt springs. Salt was important not only for the troops (food — nutrition and preservation, hide and leather processing, horses’ and other animals’ alimentation), but also for the civilian population. The army needed salt not only for its own purposes, but for distributing it in the rest of the province. However, despite the important role of the army concerning the salt resources’ protection, we have to pay attention also at he other missions the troops were charged with.